2021
DOI: 10.1111/tbed.14078
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of Blastocystis from poultry, livestock animals and humans in the southwest region of Iran—Zoonotic implications

Abstract: Blastocystis is the most common intestinal parasite found in epidemiological studies in Iran. The genus Blastocystis comprises multiple subtypes (ST), evincing the existence of extensive intrageneric diversity. Meanwhile, information on Blastocystis STs in domestic animals in Iran is limited. This study was designed to identify the prevalence and subtype distribution of Blastocystis in domestic animals and to evaluate the extent of zoonotic origin of human Blastocystis carriage. A total of 395 faecal samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Although ST14 and ST24 are often observed in various ruminant species, their presence in this study revealed that Blastocystis sp. is genetically diverse in the Alpine musk deer (Hublin et al, 2021;Maloney et al, 2019;Salehi et al, 2021). At least 13 Blastocystis STs (ST1-10, ST12, ST14, and ST24) have been identified in humans worldwide, with ST1-4 being the predominant STs and ST10, ST14, and ST24 indicating a zoonotic infection risk (Deng, Tay, et al, 2021;Jiménez et al, 2019;Khaled et al, 2020;Liu et al, 2021;Ma et al, 2020;Salehi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although ST14 and ST24 are often observed in various ruminant species, their presence in this study revealed that Blastocystis sp. is genetically diverse in the Alpine musk deer (Hublin et al, 2021;Maloney et al, 2019;Salehi et al, 2021). At least 13 Blastocystis STs (ST1-10, ST12, ST14, and ST24) have been identified in humans worldwide, with ST1-4 being the predominant STs and ST10, ST14, and ST24 indicating a zoonotic infection risk (Deng, Tay, et al, 2021;Jiménez et al, 2019;Khaled et al, 2020;Liu et al, 2021;Ma et al, 2020;Salehi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…is genetically diverse in the Alpine musk deer (Hublin et al, 2021;Maloney et al, 2019;Salehi et al, 2021). At least 13 Blastocystis STs (ST1-10, ST12, ST14, and ST24) have been identified in humans worldwide, with ST1-4 being the predominant STs and ST10, ST14, and ST24 indicating a zoonotic infection risk (Deng, Tay, et al, 2021;Jiménez et al, 2019;Khaled et al, 2020;Liu et al, 2021;Ma et al, 2020;Salehi et al, 2021). Moreover, seven STs (ST1-7) have been reported in patients in China till date (Li et al, 2021;Ma et al, 2020;Ning et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall infection rate of Blastocystis in Tibetan antelope was 4.8% (30/627) in Tibet, which was lower than the prevalence of 5.5% (6/109) and 6.0% (50/832) identified in sheep (Wang et al, 2018a;Li et al, 2018) in China and 19.3% (9/150) and 32.0% (32/100) in sheep in Iran (Rostami et al, 2020;Salehi et al, 2021). The difference in the prevalence of Blastocystis may be related to the living environment and geographical factors of different countries (Tan, 2008).…”
Section: Discussionmentioning
confidence: 73%
“…However, the existing data indicate that sheep may carry several potential Blastocystis subtypes, including ST1, ST3, ST4, ST5, ST6, and ST7 ( Tan et al., 2013 ; Song et al., 2017 ; Wang et al., 2018a ; Salehi et al., 2021 ). So far, studies on the prevalence and subtype diversity of Blastocystis in Tibetan antelope are unknown and the relevant public health impact is still unclear.…”
Section: Introductionmentioning
confidence: 99%